Alkynyl‐ or Azido‐Functionalized 1, 2, 3‐Triazoles: Selective MonoCuAAC Promoted by Physical Factors. Issue 25 (1st July 2019) - Topchiy, Maxim A.; Ageshina, Alexandra A.; Chesnokov, Gleb A.; Sterligov, Grigorii K.; Rzhevskiy, Sergey A.; Gribanov, Pavel S.; Osipov, Sergey N.; Nechaev, Mikhail S.; Asachenko, Andrey F.
Abstract: The chemical factors are tending to be the usual way to control the reaction selectivity. However, this approach is inapplicable in cases of compounds with two or more functional groups of almost the same or equal reactivity. On these occasions considering the reaction bulk physical properties can be much more beneficial. In the present work we studied one of these complicated cases, namely, the CuAAC reaction of symmetrical diazides or diynes in equimolar amounts, and developed two approaches to solve the selectivity problem between mono‐ and diaddition. Single cycloaddition in the CuAAC reaction of symmetric diazides or diynes can be achieved by: 1) precipitation of the monoaddition product, 1, 2, 3‐triazole, from nonpolar solvent – heptane; 2) the reaction halt after formation of monoaddition product due to increase of the viscosity in solvent‐free procedure. Thus, two new "green" one‐step methods of alkynyl‐ or azido‐functionalized 1, 2, 3‐triazoles synthesis were devised. Their utility was shown on 17 examples of good to excellent yields. Abstract : The concept of selectivity control by physical factors allowed to develop a facile one‐step protocol for the preparation of azido‐ or alkynyl‐functionalised 1, 2, 3‐triazoles. The reaction proceeds under mild and green conditions with equimolar amounts of starting materials.